Analysis of Problematics in Learning Nahwu from the Book of Al-Jurumiyah - Haulina, Shilfiyya; Zayinil Akhas, Muhammad (Language Development Center, 2024)
Background: This research is motivated by the gap between the importance of learning Arabic and the difficulties faced by students in learning Nahwu through the Al-Jurumiyah textbook. Purpose To determine the application of Nahwu learning methods, identify the problems of Nahwu learning, and evaluate the efforts made by educators to overcome the problems of learning Nahwu using the Al-Jurumiyah textbook for Ibtida' Awwal B students at Pondok Pesantren Padepokan Padang Ati. Method: This research uses a qualitative approach with a descriptive study design that focuses on the problems of Nahwu learning, especially in the Al-Jurumiyah textbook. Data was collected through observation and field notes. Data were analyzed using the Miles and Huberman analysis model, which includes data reduction, data presentation, and conclusion drawing. Furthermore, triangulation was carried out to ensure the validity of the data. Results and Discussion: This research identified two constraints faced by students in learning Nahwu using the Al-Jurumiyah textbook, namely linguistic constraints (difficulty in writing and reading meaning) and non-linguistic constraints (background, interest, physical condition, and classroom atmosphere). To overcome these problems, educators use simple language, provide examples, deliver easily understandable material, utilize dictionaries, and apply learning methods through games. Conclusions and Implications: This research concludes that educators have applied various Nahwu learning methods, such as the use of simple language, providing examples, and utilizing games, to overcome the linguistic (difficulty in writing and reading meaning) and non-linguistic (background, interest, physical condition, and classroom atmosphere) problems faced by students. This finding implies the importance of improving the pedagogical competence of educators in designing effective Nahwu learning according to the needs of students in Islamic boarding schools